Gambaran Karakteristik dan Pengetahuan Ibu tentang Pemberian Air Susu Ibu (ASI) Eksklusif pada Bayi Usia 6-12 Bulan - Luh Komang Sumariyanti; Luh Komang Erny Astiti; Gusti Ayu Eka Utarini (ProHealth Journal, 2026)
Breast milk is a complete and essential source of nutrition for infants and is recommended by the World Health Organization (WHO) to be provided exclusively for the first six months of life to support optimal growth and development. Despite these recommendations, the rate of exclusive breastfeeding in Indonesia remains low, contributing to an increased risk of illness and developmental issues among infants. This study aims to describe the maternal characteristics and level of knowledge regarding exclusive breastfeeding for infants aged 6–12 months at UPTD RSUD Gema Santi Nusa Penida. A descriptive quantitative design was employed using a cross-sectional approach. The study sample consisted of 43 mothers with infants aged 6–12 months who visited the hospital on May 2025. The sample size was determined using Slovin’s formula and selected through purposive sampling. Primary data were collected using a validated and reliable questionnaire. The results showed that the majority of mothers were aged between 20–35 years, were multiparous, had a middle level of education, worked as laborers or private employees, and had working hours of >8 hours per day, with a fairly good level of knowledge. Most mothers demonstrated an adequate level of knowledge about exclusive breastfeeding, despite the relatively low level of practical implementation, and a limited understanding of lactation management. It is recommended that midwives enhance lactation counseling services and expand educational efforts concerning expressed breast milk. Additionally, mothers are encouraged to actively seek reliable information sources regarding breastfeeding.